Reproductive biology of female spiny lobster Palinurus Delagoae in two areas off eastern South Africa - Greengrass, Catherine (Department of Biological Sciences, 2017)
A one-year experimental fishery for P. delagoae was established in April 2004 to determine the frequency and magnitude at which pulse fishing may be sustainable (Government Gazette 2004). Determining the extent of recovery after fishing is one aim of the experimental fishery. Assessments of the growth rate, size at sex maturity and natural mortality of P. delagoae were performed in 2000 (Groeneveld et al) and can be supplemented by the results of this study, which assess the reproductive biology of the East Coast spiny lobster in order to address this aim. A recent study (Groeneveld in press) assessed fecundity, egg loss during gestation, relative reproductive potential and lifetime egg production per recruit for P. gilchristii from three areas along the South African south coast. A general east-west trend of increasing fecundity, size at sexual maturity, and lifetime egg production per recruit was found for P. gilchristii. Examining egg-loss through the first four ( of six) developmental stages of gestation showed significant loss of around 15 % by stage four, irrespective of lobster size (Groeneveld in press). The study of fecundity in P. gilchristii ( Groeneveld in press) was used as a framework for assessing the fecundity of P. delagoae in this study.